ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA PENYAJIAN LAPORAN KEUANGAN PT. ASTINDO JAYA SAKTI BOGOR SELATAN - Juniarti, Reva; Lasmana, Andy; Kusuma, Indra Cahya (Jurnal Akuntansi Kompetif, 2025)
This research was carried out at PT. Astindo Jaya Sakti, located in Rancamaya, Bogor City. The aim of this research is to understand the process of preparing and presenting financial statements at PT. Astindo Jaya Sakti and to assess the application of SAK ETAP in relation to these financial statements. The research uses a qualitative descriptive approach, in which the author explains the process of preparing and presenting financial statements at the company and how SAK ETAP is implemented in this context. The findings reveal that the company has not fully implemented SAK ETAP, as it only reports the balance sheet, income (loss) statement, and changes in equity, without including the cash flow statement and notes to the financial statements, which are also part of SAK ETAP reporting requirements